Kwanzaa : why we celebrate it the way we do - Hintz, Martin; Hintz, Kate. (Mankato : Capstone Press, 1996)
Discusses the origins and symbols of Kwanzaa, the holiday that focuses on African American history, culture, and experiences, and offers suggestions for ways to celebrate this holiday.
Includes bibliographical references (p. 45) and index.
Keywords: Kwanzaa -- Juvenile literature; African Americans -- Social life and customs -- Juvenile literature; Kwanzaa; African Americans -- Social life and customs; United States -- Social life and customs -- Juvenile literature